Analyzing the Evolution of Sustainable Product Development Studies: A Bibliometric Review of Eco-friendly Innovation and Market Adoption - Sudirjo, Frans; Utami, Eva Yuniarti; Syahputri, Anggraini (West Science Social and Humanities Studies, 2024)
In response to escalating environmental concerns, sustainable product development has emerged as a pivotal strategy across industries. This paper presents a bibliometric review of eco-friendly innovation and market adoption within the realm of sustainable product development. The analysis spans from 1992 to 2024, synthesizing findings from 980 scholarly publications. Key themes, influential contributors, and temporal trends are identified through citation analysis, co-citation analysis, and bibliographic coupling techniques. The results underscore the significant impact of research in this field, with notable contributions addressing bio-composites, green IT, consumer behavior, and corporate sustainability. Visualizations elucidate evolving research clusters, from foundational topics to emerging areas such as circular economy and eco-innovation. Future research directions include eco-friendly materials, green product innovation, circular economy integration, sustainable product design, and supply chain implementation. This study provides valuable insights for academia, industry, and policymakers to advance environmental sustainability and socio-economic development.